The design and prototype of RUDA, a distributed grid accounting system. (10th March 2008) - Chen, Meili; Geist, Al; Bernholdt, David E.; Chanchio, Kasidit; , Daniel L. Million
The grid environment contains a large and growing number of widely distributed sites with heterogeneous resources. It is a great challenge to dynamically manage and account for usage data of grid resources, such as computational, network, and storage resources. A distributed Resource Usage Data management and Accounting (RUDA) system is designed to perform accounting in the grid environment. RUDA utilises fully decentralised design to enhance scalability and supports heterogeneous resources with no significant impact on local systems. It can easily be integrated into grid infrastructures and maintains the integrity of the grid security features.